2014
DOI: 10.5114/fn.2014.45570
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent neuroprotection of retinal ganglion cells by tempol-C8 acyl ester in a rat NMDA toxicity model

Abstract: A b s t r a c t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…A hydrophobic analog of TEMPOL, TEMPOL-C8 acyl ester was more potent (1 mg/kg) when delivered intraperitoneally in protecting RGC from NMDA-induced excitotoxic death than its hydrophilic equivalent 4-hydroxy TEMPOL. 44 Here we have performed an ivt dosing of SA-2 to the retinas to demonstrate the potency and efficacy of SA-2 in protecting against RGC death in ONC and I/R injuries. The biodistribution results showed that 2% (75 mM) of single ivt dose of compound SA-2 (vitreous concentration~15 mM) can provide 75-230 pM concentration of SA-2 to the retina and choroid in mouse eyes after 1 hour of dosing.…”
Section: Discussionmentioning
confidence: 99%
“…A hydrophobic analog of TEMPOL, TEMPOL-C8 acyl ester was more potent (1 mg/kg) when delivered intraperitoneally in protecting RGC from NMDA-induced excitotoxic death than its hydrophilic equivalent 4-hydroxy TEMPOL. 44 Here we have performed an ivt dosing of SA-2 to the retinas to demonstrate the potency and efficacy of SA-2 in protecting against RGC death in ONC and I/R injuries. The biodistribution results showed that 2% (75 mM) of single ivt dose of compound SA-2 (vitreous concentration~15 mM) can provide 75-230 pM concentration of SA-2 to the retina and choroid in mouse eyes after 1 hour of dosing.…”
Section: Discussionmentioning
confidence: 99%
“…Intravitreal administration of NMDA results in a selective RGC death in a dose-dependent manner (Nakazawa et al, 2005). After application of a dose corresponding to our experimental setting, RGC number starts to decrease after 6 h. After 24 h RGC count decrease by over 80% and after 7 days by over 90% (Manabe and Lipton, 2003; Fiedorowicz et al, 2014). After NMDA injection TUNEL-positive cells are observed both in the ganglion cell layer and the inner nuclear layer that contains both neurons (amacrine, horizontal, and bipolar cells) and glial cells (Müller cells) (Manabe and Lipton, 2003).…”
Section: Discussionmentioning
confidence: 83%
“…Retinal ganglion cell (RGC) damage was induced by intravitreal NMDA injection as we previously described (Thaler et al, 2010a; Fiedorowicz et al, 2014). Intravitreal NMDA injection induces inner retina damage by overstimulation of NMDA receptors for glutamate (i.e., excitotoxicity), the main excitatory neurotransmitter of the retinal neurons.…”
Section: Methodsmentioning
confidence: 99%